Changes in the molecular structure and stability of β-lactoglobulin induced by heating with sugar beet pectin in the dry-state. (August 2020) - Qi, Phoebe X.; Wickham, Edward D.
Abstract: We have shown previously that dry-heating whey protein isolate (WPI) and sugar beet pectin (SBP) leads to a noticeable improvement in the physical, chemical, and emulsion stabilization capacity of WPI. To discern the role of β-lactoglobulin (β-LG), the major protein of WPI, played at the molecular level in the observed functional properties, we investigated, in detail, the changes that occurred in the molecular structure and thermal stability of β-LG as a result of heating with SBP in the dry state. Far-UV CD spectroscopy analysis revealed that nearly all secondary structural elements of β-LG were affected slightly by dry-heating alone. Varying mass ratios of SBP, 1:0, 5:1, 3:1, 2:1, 1:1, and 0:1 β-LG:SBP did not significantly impair the structural integrity and thermal stability of β-LG. The tertiary structure of β-LG, however, experienced considerable disruption as probed by near-UV CD and Trp intrinsic fluorescence spectroscopy. Despite the non-radiative nature of the FRET complexes formed between β-LG and SBP, a donor-acceptor relationship was established by the detection of fluorescence lifetimes corresponding to their distinctive excited states. Unlike the case of dry-heated WPI and SBP mixtures, the protection of the tertiary structure of β-LG was insufficient by reacting with SBP. Such deficiency suggested that the presence and involvement of other proteins in WPI are essential in developing the interacting complexes and conjugates with the remarkable stability as determined. Graphical abstract: Image 1 Highlights: Secondary structure of β-LG was not affected by dry-heating with SBP. The β-LG and SBP complexes hardly showed FRET. Tertiary structure and Trp environment of β-LG were disrupted by reacting with SBP. Thermal stability of β-LG molecular structure was improved by all levels of SBP. Reacting with β-LG greatly increased the thermal stability of feruloyl groups of SBP.